Mental Training Process for Disabled Athletes at the The Garden of Winangun Special School , Kebumen - Burhaein, Erick; Perkasa, Catur Yuda (Journal of Physical and Outdoor Education, 2024)
The aim of this study was to determine the mental training process of athletes. disability School Outside Usually in Tamanwinangun Kebumen . The method chosen use descriptive qualitative with researcher as instrument main . Data collection was obtained with observation , interviews and documentation . The sources originate from one of the teachers or coach School Outside Normal Taman Winangun Kebumen . Research done in the month March 2024. After the data is obtained furthermore analyzed in narrative data form with reduce data, present data, and draw conclusions a conclusion . Triangulation chosen as technique Data validity . Research results This show that athlete disability School Outside Normal Taman Winangun Kebumen has carry out so Lots mental exercise where exercise This make athletes​ more believe self , behave optimistic and calm in face match so that capable adapt existing conditions